A interação em um processo de formação contínua de professores - Tessari, Daisy Maria da Silva (2015)
The aim of this paper is to analyze and critically understand, in a context of continuing teacher education, the interactions between an educator-researcher and a Portuguese language teacher in education, which focus was to empower the teacher for preparing ninth grade students from a municipal school in Rio de Janeiro to attend the test Prova Brasil from the National System of Basic Education Evaluation. This study s theoretical framework is founded on the Vygotskyan socio-historical-cultural perspective (VYGOTSKY, 1934/2009, 1935/2007), based on the dialogism and the verbal interaction (BAKHTIN, 1929/1995; VYGOTSKY, 1934/2009, 1935/2007), on the trigger of discussion about the discursive dynamics in contexts of critical collaborative teachers education, focusing on the authoritative and internally persuasive discourses (BAKHTIN, 1929/1995), and also on the collaboration and creation of zones of proximal development (VYGOTSKY, 1935/2007; NEWMAN; HOLZMAN, 2005; MAGALHÃES, 2009-2011). In methodological terms, it is inserted in the critical paradigm and organized as a Critical Collaborative Research (MAGALHÃES, 2009-2011). The corpus of this investigation is composed by interactions between an educator-researcher and a Portuguese language teacher, recorded during continuing teacher education meetings. In the perspective of Applied Linguistics, data were analyzed through participants speech materiality, in the light of categories that consider verbal interaction as essential reality of language. For this purpose, linguistic and discursive categories were used (NEVES, 2006; NININ, 2013; LIBERALI, 2013; HALLIDAY; HASSAN 1976; KOCH, 2003, 2014). This survey results point out to the idea that the critical collaborative management and the internally persuasive discourse enable the participants voices turnover through verbal interaction, which can lead to the creation of zones of proximal development. However, they also reveal that comfortable collaboration and authoritative discourse reduce or exclude the possibilities of negotiation and interlacing of voices